ANALYZING THE INFLUENCE OF TRAINING AND DEVELOPMENT ON ORGANIZATIONAL PERFORMANCE AT PT. BANK TABUNGAN NEGARA (PERSERO) TBK MANADO - Derek, Vivian Febriani; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2014)
Nowadays human resource is a crucial things, so that many company implement training and development for their employees to face the competition. The objectives of this research are to analyze the influence of Training and Development on Organizational Performance at PT. Bank Tabungan Negara (Persero) Tbk, Manado. This is a quantitative research that associative with multiple linear regression analysis technique. The population in this study is the employees at PT. Bank Tabungan Negara (Persero) Tbk, Manado and the respondents are 30 peoples. This study may imply that the contribution of Training Design, On the Job Training, and Delivery Style on Organizational Performance of 86% while the remaining 14% is affected by other variables not examined in this study. For PT. Bank Tabungan Negara (Persero) Tbk, Manado in the managerial role should care about the Influence of Training and Development on Organizational Performance so that through this research the company can get more information about the fact which happens and company may improve the human resource practice especially in training and development. Keywords: training and development, organizational performance